2018
DOI: 10.1002/lary.27086
|View full text |Cite
|
Sign up to set email alerts
|

Safety of high‐current stimulation for intermittent intraoperative neural monitoring in thyroid surgery: A porcine model

Abstract: Objectives During monitored thyroidectomy, displacement of the recurrent laryngeal nerve (RLN) or vagus nerve (VN) in some complicated cases can increase the risk of injury. Although increasing the stimulus current can facilitate nerve mapping and localization, the safety of a high‐current stimulus remains unknown. Therefore, this study evaluated the safety of a high‐current stimulus in a porcine model. Methods Short‐duration (1 minute), high‐current (3, 5, 10, 15, 20, 25, and 30 mA at 4Hz) stimulus pulses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…14 Increasing current to 2 or 3 mA may expedite displaced VN mapping in the carotid sheath and provide higher amplitudes. 18,21,22 The study lacks stimulation data regarding the EBSLN. Additionally, the right and left nerve data were pooled data of all patients and not compared in the same patient.…”
Section: Discussionmentioning
confidence: 99%
“…14 Increasing current to 2 or 3 mA may expedite displaced VN mapping in the carotid sheath and provide higher amplitudes. 18,21,22 The study lacks stimulation data regarding the EBSLN. Additionally, the right and left nerve data were pooled data of all patients and not compared in the same patient.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Chavez et al 6 concluded that a harmonic scalpel did not cause any significant thermal damage to the RLN, even when it was activated close to the nerve (up to 1 mm) or when the nonactive blade was placed at the nerve. Furthermore, Lu et al 10 revealed that the application of a short-duration, high-current stimulating pulse to the VN or RLN during monitored thyroidectomy had no harmful effects. With the NP device, the incision distance was 20 mm, and the short incision time might prevent nerve damage.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have attempted to overcome these issues and have reported on resection around the RLN using energy devices. [6][7][8][9][10][11][12][13] Olympus Corporation (Tokyo, Japan) recently developed the new hybrid pencil type energy (NP) device. This device allows surgeons to perform coagulation, cutting, and dissection during surgery with both ultrasonically generated energy and electrically generated energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, most training programs and research use mediumsized animals for experimental models, most typically canine (dog) models (56)(57)(58)(59) and porcine(swine/mini-pig) models (60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77). Dog models of laryngeal function and the RLN are well-established and closely mimic the anatomy, size, and physiology in humans.…”
Section: Animal Modelsmentioning
confidence: 99%